1999
DOI: 10.1108/09564239910288987
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the cross‐cultural applicability of a service quality measure A comparative study between Quebec and Peru

Abstract: This research assesses the psychometric properties of a service quality measure applied internationally and investigates cross-cultural differences in perceived service quality between North American and Latin American consumers. With this purpose in mind a crosscultural survey was conducted in which consumers evaluated the quality of supermarket services both in Quebec and in Peru. Four culture value orientations were expected to account for differences in perceived service quality: individualism, collectivis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(14 citation statements)
references
References 52 publications
0
13
0
1
Order By: Relevance
“…A sample size of 300 was chosen for this study, keeping in mind the average size of samples used by other researchers in similar studies such as Alrubaiee and Alkaa'ida, (2011) (Espinoza, 1999). The criterion of inclusion in this study is the local and foreign outpatients who have utilized the health care services at the private hospitals within the last 12 months.…”
Section: Sample Selection and Sample Sizementioning
confidence: 99%
“…A sample size of 300 was chosen for this study, keeping in mind the average size of samples used by other researchers in similar studies such as Alrubaiee and Alkaa'ida, (2011) (Espinoza, 1999). The criterion of inclusion in this study is the local and foreign outpatients who have utilized the health care services at the private hospitals within the last 12 months.…”
Section: Sample Selection and Sample Sizementioning
confidence: 99%
“…The effectiveness of PCSR on PCR (H1) was not always confirmed. In Brazil, China, and South Africa—that is, collectivistic countries (Donoghue et al, ; Morales Espinoza, ; Zhang et al, )—PCSR was found to be significant and positive when directly relating with PCR, whereas in the Russia and India—that is, individualistic countries (Mattila, ; Morgeson et al, )—it was not found to be significant.…”
Section: Discussionmentioning
confidence: 99%
“…Collectivistic cultures emphasise individuals' cooperation, favouring the importance of the group's objectives instead of those of the individual, and tend to behave in accordance with social norms (Liu & McClure, ; Morales Espinoza, ). Consequently, consumers from collectivistic cultures tend to emphasise the importance of activities that favour social responsiveness and, thus, PCSR.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, in terms of discriminant validity (see Table 5), Espinoza (1999) considered the average variation extraction value of a certain latent variable must be larger than the square of the correlation coefficient of a random pair of latent variables on non-diagonal. This is called having discriminant validity capacity.…”
Section: < Table 4 About Here>mentioning
confidence: 99%